Incidence of Early Surgical Site Infection (SSI) in Elective Orthopaedic Implant Surgeries (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To evaluate the frequency of SSI and isolated infectious micro-organisms with length of hospital stay.Methods: Patients with closed fractures planned for elective surgeries admitted in Orthopaedic department from February 2017 till July 2017. Data of this retrospective descriptive study was recorded on a proforma covering patient’s demographics, length of hospital stay, provisional diagnosis, procedure performed, culture sent and micro-organism isolated. Total 155 patients male and female, age range 5- 75 years were included. Exclusion criteria were patients with open injuries, soft tissue operations, emergencies, non-implant surgeries, comorbid patients (other than hypertension). This data was analyzed for frequency and percentages of the variables.Results: 155 patients of age were grouped into 3 categories. Out of which, 119(76.77%) male and 36(23.23%) were female. Among these, infectious micro-organisms isolated from 11(7.09%) patients. Klebsiella species found to be most prevalent in 4(36.36%) followed by pseudomonas aeruginosa 3(27.27%), Coagulase negative staphylococci 3(27.27%) and Methicillin susceptible S. aureus 1(9.09%) in the descending order. 6(54.54%) of these patients were treated in the ward for more than 2 weeks and most common isolate in correlation with the prolong stay was pseudomonas aeruginosa.Conclusion: The incidence of SSI in elective procedures for closed fractures was found in 11 (7.09%) with Klebsiella species being the most common. On the other hand, Pseudomonas aeruginosa was found to be most prevalent in patients with prolong hospital stay which could be due to nosocomial abundance and pre-operative colonization.